2019
DOI: 10.1159/000499641
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>IKZF1</i></b> Gene Deletion in Pediatric Patients Diagnosed with Acute Lymphoblastic Leukemia in Mexico

Abstract: The IKZF1 gene is formed by 8 exons and encodes IKAROS, a transcription factor that regulates the expression of genes that control cell cycle progression and cell survival. In general, 15-20% of the patients with preB acute lymphoblastic leukemia (preB ALL) harbor IKZF1 deletions, and the frequency of these deletions increases in BCR-ABL1 or Ph-like subgroups. These deletions have been associated with poor treatment response and the risk of relapse. The aim of this descriptive study was to determine the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…However, other studies observed differences in IKZF1 large segment deletion frequency: 12% in German patients, 20.6% in Mexico patients, 16% in Swedish patients, and 28.6% in American patients. IKZF1 SNV and small InDel mutation in our study was 2.5%, almost close to the proportion reported in the literature (<1%) ( Mullighan et al, 2008 ; Dorge et al, 2013 ; Ofverholm et al, 2013 ; Ayon-Perez et al, 2019 ; Stanulla et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, other studies observed differences in IKZF1 large segment deletion frequency: 12% in German patients, 20.6% in Mexico patients, 16% in Swedish patients, and 28.6% in American patients. IKZF1 SNV and small InDel mutation in our study was 2.5%, almost close to the proportion reported in the literature (<1%) ( Mullighan et al, 2008 ; Dorge et al, 2013 ; Ofverholm et al, 2013 ; Ayon-Perez et al, 2019 ; Stanulla et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Deficiencies from these sites, such as the entire gene (including exons 1–8), or focal gene (including exons 2 and/or 8), or untranscriptional regulatory regions (including exon 1), can lead to IKZF1 hypofunction ( Iacobucci & Mullighan, 2017 ). The deletion of exons 4–7, lacking the ability to bind DNA, was a negative domain and thus led to leukemia ( Mullighan et al, 2008 ; Iacobucci et al, 2009 ; Chiaretti et al, 2016 ), which was the most common deletion pattern of IKZF1 in our cohort (36%), consistent with results in Germany, Japan, Sweden and the US and different from results in Mexico, where the deletion of exon 1 (85%) occurred most frequently ( Ayon-Perez et al, 2019 ). Although SNV or small InDel mutations of IKZF1 were infrequent and present, their molecular consequences could be either haploid insufficiency or dominant negative effects, as with deletions.…”
Section: Discussionsupporting
confidence: 88%
“…Ayón-Perez et al. found that 20.6% (36 cases) ( 37 ), while Rosales-Rodríguez et al. ( 38 ) detected 27% (63 cases) both using MLPA.…”
Section: Discussionmentioning
confidence: 98%
“…It is this phenomenon that sparks the possibility that aberration in any IKZF gene may contribute to leukemogenesis by perturbing the transcriptional networks of IKZF genes normal functions including lymphoid maturation, tumor suppression, cell-cycle regulation, kinase signaling and chromatin modification ( 108 ). Early reports associated germline IKZF1 deletions with poorer treatment responses and unfavorable outcomes ( 114 116 ), while more recent studies found the converse to be true, with beneficial responses to induction therapy ( 117 ).…”
Section: Gene-specific Mechanisms Of Oncogenicitymentioning
confidence: 99%